Disruption of Apyrases Inhibits Pollen Germination in Arabidopsis - Steinebrunner, Iris (American Society of Plant Biologists, 2003)
In Arabidopsis, we previously identified two highly similar apyrases, AtAPY1 and AtAPY2. Here, T-DNA knockout (KO) mutations of each gene were isolated in a reverse genetic approach. The single KO mutants lacked a discernible phenotype. The double KO mutants, however, exhibited a complete inhibition of pollen germination, and this correlated with positive β-glucuronidase staining in the pollen of apyrase promoter:β-glucuronidase fusion transgenic lines. The vast majority of the pollen grains of these mutants were identical to wild type in size, shape, and nuclear state and were viable as assayed by metabolic activity and plasma membrane integrity. Complementation with either AtAPY1 or AtAPY2 cDNA rescued pollen germination, confirming that the phenotype was apyrase specific. Despite the redundancy of the two apyrases in rescue potential, transmission analyses suggested a greater role for AtAPY2 in male gamete success. The effect of mutant apyrase on the transmission through the female gametophyte was only marginal, and embryo development appeared normal in the absence of apyrases. The male-specific double KO mutation is fully penetrant and shows that apyrases play a crucial role in pollen germination.